2012
DOI: 10.3354/meps09489
|View full text |Cite
|
Sign up to set email alerts
|

Wave attenuation by submerged vegetation: combining the effect of organism traits and tidal current

Abstract: Accurate wave height prediction along the shore plays an important role in coastal protection and management. To account for the effect of submerged vegetation in waveattenuation models, it is important to understand how the interaction between vegetation characteristics and hydrodynamic forcing affects wave attenuation. To determine the effect of vegetation characteristics, we used seagrass mimics that varied in (1) blade stiffness, (2) shoot density and (3) leaf length; to investigate the effect of hydrodyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(125 citation statements)
references
References 39 publications
(61 reference statements)
5
118
1
1
Order By: Relevance
“…For example, some studies have attempted to account for plant stiffness or v www.esajournals.org swaying motion, but still estimated drag coefficients similar to those obtained with our model (Méndez et al 1999, Bradley andHouser 2009). On the other hand, other studies have found that stiffness and plant dynamic response to the flow is important (Bouma et al 2010, Riffe et al 2011, Paul et al 2012, and plant flexibility may help explain why attenuation appears to vary with wave period (Bradley and Houser 2009).…”
Section: Importance Of Reynolds Number For Coastal Protectionmentioning
confidence: 77%
See 1 more Smart Citation
“…For example, some studies have attempted to account for plant stiffness or v www.esajournals.org swaying motion, but still estimated drag coefficients similar to those obtained with our model (Méndez et al 1999, Bradley andHouser 2009). On the other hand, other studies have found that stiffness and plant dynamic response to the flow is important (Bouma et al 2010, Riffe et al 2011, Paul et al 2012, and plant flexibility may help explain why attenuation appears to vary with wave period (Bradley and Houser 2009).…”
Section: Importance Of Reynolds Number For Coastal Protectionmentioning
confidence: 77%
“…Our bulk drag coefficient v www.esajournals.org contained the effects of all processes not captured by Eqs. 1 and 2, including stem swaying (Méndez et al 1999), stiffness (Paul et al 2012), and interactions among stems (Mendez and Losada 2004).…”
Section: Calculating the Bulk Drag Coefficient Of Vegetation On Wavesmentioning
confidence: 99%
“…Seagrass meadows modify the benthic boundary layer, which manifests in changes in mean velocities, orbital velocities and turbulence (Granata et al 2001, Infantes et al 2012, Ros et al 2014). This modification is generally understood to be moderated by the architectural characteristics of the meadow (both shoot density and number of leaves per shoot) and the plants (shoot biomass, leaf length, leaf width, blade stiffness) (Borg et al 2005, Peralta et al 2008, Paul et al 2012. The presence of gaps within a canopy reduces the capacity of meadows to attenuate waves and turbulence (Boudouresque et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Flume studies have shown that differences in vegetation structure, density, and flexibility affect the measured amount of wave attenuation (Bouma et al, 2010;Paul et al, 2012;Blackmar et al, 2014). While modeled wave attenuation is most simply described by stem density, height, and diameter (Dalrymple et al, 1984;Kobayashi et al, 1993), more robust models include stem flexibility (Asano, 2006;Mullarney and Henderson, 2010) and variations in the structure of the vegetation (Dubi and Torum, 2011).…”
Section: Introductionmentioning
confidence: 98%